Pelaksanaan Administrasi Kepegawaian dalam Meningkatkan Mutu Pendidikan di Madrasah Ibtidaiyah - Nurul ‘Ilmi Azizah, Annafi’; Luthfi Maghfiroh, Laila; Aslam Azzahra, Luthfiya; Fajar, Malik; Tasya Kamila, Marshanda (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Personnel administration is a crucial aspect in the management of educational institutions, as it plays a role in creating a conducive work environment and improving the quality of education. This research aims to analyze the personnel administration system at Madrasah Ibtidaiyah Negeri (MIN) 3 Sukoharjo, focusing on the personnel system and the employee recruitment process. The research method used is descriptive qualitative, with data collection techniques through observation and interviews with the head of the madrasa, administrative staff, and teachers responsible for personnel management. The research results show that the personnel administration at MIN 3 Sukoharjo has implemented a digital system through the SIMPATIKA application managed by the Ministry of Religious Affairs. The employee recruitment process is carried out systematically through stages of administrative selection, written tests, psychological tests, and interviews. In addition, the personnel system at this madrasa also includes the development of educators, management of employee welfare, and digital-based performance evaluation. Good personnel administration contributes to the improvement of education quality through the selection of competent educators, the implementation of innovative teaching methods, and more optimal student learning outcomes. However, challenges such as limited resources and recruitment policies still pose obstacles. Therefore, more adaptive strategies are needed in managing educational staff to improve administrative effectiveness and the quality of education in madrasahs.